A brevidade da vida: encontros com morte em Sandman de Neil Gaiman - Andrade, Jaqueline Gomes Ribeiro de (2024)
Sandman is a series of comic books in which Sandman, the king of dreams and ruler of dreaming, his kingdom, is the main character. The stories take place while he performs his functions of making living creatures dream and interacts with his brothers, the perpetual ones, who also have functions linked to humanity. One of his sisters is Death, who performs the function of ending life. It is from the stories of Death as a source-object that reflections on inspirations for life, aesthetics, meaning of life and eternalization of life through art are constructed, themes present in this investigation. Humans need devices to face the great anthropological gap that is death and that is why they construct narratives. The main objective of this work is to reflect on the character Death from the Sandman comics by Neil Gaiman, British author of the fantasy literature genre, as a literary reference for calming responses to the tragedy of death in human life. Edgar Morin, together with other authors, is used as the main theoretical-methodological contribution of this research, to understand death as part of life and the contribution of literature as an important strategy for understanding the subject in relation to death. Edgar Morin, points to aesthetics as a potential enricher of the human condition capable of blossoming the sublimity that produces enchantment and easing the concerns of living, such as the pain caused by existential uncertainty. As a result, inspirations for life in the face of death are highlighted, the aestheticization of death experiences as a means capable of mitigating, filling the anthropological gap of death and the eternalization of existence through art.